2015
DOI: 10.1002/cncr.29419
|View full text |Cite
|
Sign up to set email alerts
|

Impact of complications on long‐term survival after resection of intrahepatic cholangiocarcinoma

Abstract: BACKGROUND:The impact of postoperative complications on the long-term outcomes of patients undergoing surgery for cancer is unclear. The objective of the current study was to define the incidence of complications among patients undergoing surgery for intrahepatic cholangiocarcinoma (ICC) and identify the association between morbidity and long-term outcomes. METHODS: A total of 583 patients undergoing surgery with curative intent for ICC between 1990 and 2013 at 1 of 12 participating institutions were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 41 publications
2
60
0
Order By: Relevance
“…Some authors had reported an improved survival over time for the past few years, however, this might be attributed to improved non-surgical therapy or more careful selection of candidates for surgical resection [74] . Postoperative complications were found to be independent predictors of worse long-term outcomes (hazard ratio [HR], 1.64; 95% CI, 1.30-2.08), and the outcome worsens with increased severity of the complications [75] . Outcomes of ICC depend on disease stage (especially the presence or absence of node involvements and vascular invasion) and status of surgical margins, rather than size [72] .…”
Section: Outcomes After Resectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors had reported an improved survival over time for the past few years, however, this might be attributed to improved non-surgical therapy or more careful selection of candidates for surgical resection [74] . Postoperative complications were found to be independent predictors of worse long-term outcomes (hazard ratio [HR], 1.64; 95% CI, 1.30-2.08), and the outcome worsens with increased severity of the complications [75] . Outcomes of ICC depend on disease stage (especially the presence or absence of node involvements and vascular invasion) and status of surgical margins, rather than size [72] .…”
Section: Outcomes After Resectionmentioning
confidence: 99%
“…Patients who had a positive-margin (R1) resection had higher risk of recurrence (HR, 1.61; 95% CI, 1.15-2.27) and shorter overall survival (OS) (1.54; 1.12-2.11) than those with R0 resection [80] . Stage-stratified 5-year survivals according to the 7 th edition of the AJCC staging system were 32% for all patients enrolled, 62% for stage I (T1N0), 27% for stage II (T2N0) and 14% for stage III (T3N0, T1-3, N1) in a French study of 163 patients undergoing potentially curative surgery [73] .…”
Section: Outcomes After Resectionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1417] Most EHBM require a major surgical procedure, which can involve a liver resection, removal of the extrahepatic biliary tree, or a pancreatoduodenectomy. [1] Peri-operative outcomes following these extensive operations can be associated with considerable morbidity, with post-operative complications as high as 30–40% in many centers.…”
Section: Introductionmentioning
confidence: 99%